Sickle Retinopathy in a Person with Hemoglobin S/New York Disease - Donovan Calder; Maryse Etienne-Julan; Marc Romana; Naomi Watkins; Jennifer M. Knight-Madden (Case Reports in Genetics)
A patient who presented with sickle retinopathy and hemoglobin electrophoresis results compatible with sickle cell trait was found, on further investigation, to be a compound heterozygote with hemoglobin S and hemoglobin New York disease. This recently reported form of sickle cell disease was not previously known to cause retinopathy and surprisingly was observed in a non-Asian individual. The ophthalmological findings, the laboratory diagnosis, and possible pathophysiology of this disorder are discussed. Persons diagnosed with sickle cell trait who present with symptoms of sickle cell disease may benefit from specific screening for this variant.